Dynamic mode coupling in terahertz metamaterials - Su, Xiaoqiang (2015)
The near and far field coupling behavior in plasmonic and metamaterial systems have been extensively studied over last few years. However, most of the coupling mechanisms reported in the past have been passive in nature which actually fail to control the coupling mechanism dynamically in the plasmonic metamaterial lattice array. Here, we demonstrate a dynamic mode coupling between resonators in a hybrid metal-semiconductor metamaterial comprised of metallic concentric rings that are physically connected with silicon bridges. The dielectric function of silicon can be instantaneously modified by photodoped carriers thus tailoring the coupling characteristics between the metallic resonators. Based on the experimental results, a theoretical model is developed, which shows that the optical responses depend on mode coupling that originates from the variation of the damping rate and coupling coefficient of the resonance modes. This particular scheme enables an in-depth understanding of the fundamental coupling mechanism and, therefore, the dynamic coupling enables functionalities and applications for designing on-demand reconfigurable metamaterial and plasmonic devices.